Development of E-Learning Content on Corrosion Based on Flex Discovery Learning Approach for Senior High School - Rahmi Eka Witri; Citra Girsang; Anna Mariana Situngkir; Dian Fitriyani (Center For Advanced Material Processing, Artificial Intelligence, Biophys-Informatics (CAMPBIOTICS), Universitas Negeri Padang, 2022)
The COVID-19 pandemic has affected the education system in Indonesia, one of which is the implementation of learning from home policies. To assist the learning process, corrosion e-learning based on flex discovery learning has been developed for senior high school. This research is a research and development with 4D model. E-learning has been validated by three validators and tested for practicality by 10 students of SMA Negeri 2 Pasaman, West Sumatra, Indonesia. Data were analyzed by Aiken V and the percentage of students' understanding, using instruments in the form of validity and practicality questionnaires. the average value of V content and construct validity test results was 0.86 and 0.88 and for practicality the average value was 0.83. These data prove that the developed e-learning is valid and practical so that it can be used in the learning process.